Gender entrepreneurship in Latin America: Does the institutional system matter? - Guillen, J. (2022)
This study attempts to uncover the institutional determinants of female entrepreneurship in a set of eight Latin American countries. Following the institutional system classification in the literature, we grouped the set of countries into three categories: State-Led, Emerging Liberal Market, and Family Led. We then split the data panel into two different groups: Argentina, Bolivia, Ecuador, and Venezuela, which are mostly State-Led; the other group includes Brazil, Chile, Colombia, Mexico, and Peru, which are either Family Led or Emerging Liberal Market Oriented where the degree of State intervention in the economy is lower. Our research investigated these institutional determinants of female entrepreneurship using a set of socioeconomic, cognitive, and macroeconomic variables. Our findings offer a new perspective on gender entrepreneurship in Latin America, considering internal and external factor. The first considers institutional varieties and the latter macroeconomic effects. This is relevant in order to find relevant incentives of entrepreneurship by gender.